Pengajuan Grasi yang Berulang-ulang dalam Perspektif Hukum Pidana Islam - Santoso, Santoso (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The paper aims to answer questions about how the procedure for filing clemency under Law No. 22 of 2002, as well as what are the consequences of repeatedly filing clemency by death convicts, and how Islamic law evaluates it. The results of this study concluded that the procedure for filing clemency according to Law no. 22 of 2002 creates more legal certainty for convicts who want to apply for clemency regarding the requirements and the time frame, because it stipulates the timeframe and procedures for completing the clemency request for each agency. Meanwhile, repeated applications for clemency will have an impact on the convict's psyche, because the submission is not necessarily accepted. What is clear is that the legal process will be protracted, then hinders the enforcement of the rule of law. Whereas in Islamic law, clemency is up to the victim's guardian, whether to accept or reject his apology. Whereas in Islamic law, the exclusion postponed is only when the guardian is in a crazy state and is not yet mature, then waiting to recover and mature